2021
DOI: 10.1111/icad.12555
|View full text |Cite
|
Sign up to set email alerts
|

Temperature drives variation in flying insect biomass across a German malaise trap network

Abstract: Among the many concerns for biodiversity in the Anthropocene, recent reports of flying insect loss are particularly alarming, given their importance as pollinators, pest control agents, and as a food source. Few insect monitoring programmes cover the large spatial scales required to provide more generalizable estimates of insect responses to global change drivers. We ask how climate and surrounding habitat affect flying insect biomass using data from the first year of a new monitoring network at 84 locations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 81 publications
6
37
0
Order By: Relevance
“…Temperature and radiation are strongly coupled, in particular during the summer period [ 45 , 46 ]. Both were observed to positively influence insect activity rates in earlier studies [ 1 , 8 , 11 ], with ambient temperature having a direct effect on body temperature and thus flight ability [ 47 ]. However, other studies reported that at above-average temperatures in the summer months, the linear relationship breaks down and activity decreases [ 8 , 14 ], so that a temperature optimum curve could actually have been expected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperature and radiation are strongly coupled, in particular during the summer period [ 45 , 46 ]. Both were observed to positively influence insect activity rates in earlier studies [ 1 , 8 , 11 ], with ambient temperature having a direct effect on body temperature and thus flight ability [ 47 ]. However, other studies reported that at above-average temperatures in the summer months, the linear relationship breaks down and activity decreases [ 8 , 14 ], so that a temperature optimum curve could actually have been expected.…”
Section: Discussionmentioning
confidence: 99%
“…A significant loss of biodiversity and biomass is reported, the reasons for which are attributed to habitat destruction, intensified agriculture, invasive organisms, and climate change [ 4 ]. To be able to record the further course of these trends and the reasons responsible for them, systematic monitoring of terrestrial insects, as it is performed in only a few monitoring programs [ 6 , 7 , 8 , 9 ], is essential. However, in addition to the long-term influences of, e.g., agriculture and climate change, environmental and methodological conditions during sampling could have a direct effect on the insect diversity collected and should thus be considered when evaluating data from ecological surveys [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations